(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The article shows that the composition of the fabric is 100% higher than that of polyester and single-layer bed fabrics, and the residual (plastic) deformation is lower than that of other bed fabrics with a support surface and fiber content.